Pendekatan Filsafat Ilmu Terhadap Perkembangan Deep Learning dalam Perspektif Aksiologi: Philosophy of Science Approach to the Development of Deep Learning in Axiological Perspective - Budi Triandi; Muhammad Zarlis; Zulkifli Nasution; Akbar, Muhammad Barkah; Wahyuni, LInda (Computer Science Research and Its Development Journal, 2023)
Deep learning is part of the most popular artificial intelligence (AI) technology among the public where this research aims to assist in solving problems. This study discusses the relationship between the philosophy of science and the correlation of axiology on the development of deep learning. This study uses library research by collecting literature studies, analyzing data, describing the contents of the problem, concluding the problem, providing conclusions and suggestions. The basis for implementing knowledge about deep learning can recognize objects or sounds with the science under study and the correlation between axiology and the development of deep learning trials, the need for deep learning in an increasingly complex society becomes the basis for developing systems where data processing is carried out in more detail. and produce the correctness according to the algorithm that has been inputted. The research discussed also provides suggestions for guidance on the development of deep learning science on the development of axiology related to the philosophy of science in the implementation of deep learning systems on the development of science and technology in the field of computers.